1999
DOI: 10.1074/jbc.274.30.21063
|View full text |Cite
|
Sign up to set email alerts
|

Long QT Syndrome-associated Mutations in the S4-S5 Linker of KvLQT1 Potassium Channels Modify Gating and Interaction with minK Subunits

Abstract: Long QT syndrome is an inherited disorder of cardiac repolarization caused by mutations in cardiac ion channel genes, including KVLQT1. In this study, the functional consequences of three long QT-associated missense mutations in KvLQT1 (R243C, W248R, E261K) were characterized using the Xenopus oocyte heterologous expression system and two-microelectrode voltage clamp techniques. These mutations are located in or near the intracellular linker between the S4 and S5 transmembrane domains, a region implicated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 27 publications
7
67
0
Order By: Relevance
“…6, which is published as supporting information on the PNAS web site). Similar effects of S4-S5 loop mutations on voltage dependence have been reported for other voltage-gated potassium channels, such as for Shaker (28) and KCNQ1 (29).…”
Section: Mimicking the Dephosphorylated State Of The S4 -S5 Loop Thresupporting
confidence: 49%
See 1 more Smart Citation
“…6, which is published as supporting information on the PNAS web site). Similar effects of S4-S5 loop mutations on voltage dependence have been reported for other voltage-gated potassium channels, such as for Shaker (28) and KCNQ1 (29).…”
Section: Mimicking the Dephosphorylated State Of The S4 -S5 Loop Thresupporting
confidence: 49%
“…1). Because the S4-S5 loop has been shown to influence channel conductance and gating (28,29), we hypothesized that the addition of a phosphate group here, with its negative charge, could modulate the activity of the channel.…”
Section: Evidence For Phosphorylation In the S4 -S5 Loop Of Kcnq2͞kcnq3mentioning
confidence: 99%
“…Sanguinetti and co-workers (50,51) have similarly demonstrated a significant role for the S4-S5 linker region in coupling channel voltage sensing with activation in the HCN pacemaker channels. Finally, in the KvLQT channel family, mutations within the S4-S5 linker region cause a decrease in current and modify channel interactions with the minK ␤-subunit, increasing the likelihood of long QT syndrome (52). We have demonstrated here for the first time that this region is also crucial for the trafficking of a class of non-voltage-gated K ϩ channels, the Ca 2ϩ -activated IK and SK channels.…”
Section: Discussionmentioning
confidence: 82%
“…Franqueza et al reported a W248R-KCNQ1 mutation; the same position as our mutation but a different amino acid change. 19 Without KCNE1, the W248R-KCNQ1 channel produced reduced current densities compared to WT-KCNQ1 and displayed no dominant negative effect. And the co-expression of mutant KCNQ1 with KCNE1 caused a marked suppression of IKs current.…”
Section: Mutations In W248 Residue Alter the Gating Properties Of Thementioning
confidence: 99%
“…Recent studies demonstrated that KCNQ1 mutations in the intracellular S4-S5 linker affected the voltage sensitivity of the reconstituted channels. 19 Fig 3C represents the voltage-dependence of current activation. Tail current densities after each test potential were fitted to Eqn 1 (see methods).…”
Section: Characterization Of the Biophysical Properties Of W248f Kcnq1mentioning
confidence: 99%